2016
DOI: 10.1111/modl.12346
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Proficiency or Short‐Term Memory? Validation of an Elicited Imitation Test for SLA Research

Abstract: Elicited imitation requires listeners to listen and repeat sentences as accurately as possible. In second language acquisition (SLA) research it has been used for a variety of purposes. Recently, versions of the same elicited imitation test (EIT) have been created in 6 languages with the purpose of measuring second language proficiency (Ortega et al., ; Tracy–Ventura et al., 2014; Wu & Ortega, ). The validity of these EITs has been tested, and results are promising. However, questions remain regarding the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
89
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(103 citation statements)
references
References 39 publications
12
89
2
Order By: Relevance
“…Similar results were found in Kim et al. (), which developed and validated a Korean EIT following Ortega et al.’s () design and explored the role of PSTM in EIT performance. A total of 66 L2 learners across three course levels (beginner, intermediate, and advanced) took the Korean EIT, listening and speaking tests, and a PSTM test.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Similar results were found in Kim et al. (), which developed and validated a Korean EIT following Ortega et al.’s () design and explored the role of PSTM in EIT performance. A total of 66 L2 learners across three course levels (beginner, intermediate, and advanced) took the Korean EIT, listening and speaking tests, and a PSTM test.…”
Section: Introductionsupporting
confidence: 84%
“…Similar findings have been corroborated by SLA studies such as Kim et al. () and Okura and Lonsdale (), which indicated that EITs highly correlated with other measures of L2 proficiency but not WM scores. Okura and Lonsdale () administered a 60‐item English EIT and a 10‐item WM test to L2 learners ( n = 40) across six course levels (Levels 0–5).…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations